The Labyrinth of The Iron Cage of Educational Capitalism: The Reflection of Siri Na Pacce in Strengthening Educational Leadership - Nadeak, Bernadetha; Wiryadinata, Halim (International Journal of Educational Management and Innovation, 2024)
This study aims to demonstrate that the Indonesian local culture, Siri Na Pacce, becomes the construction of educational leadership in the era of educational capitalism. The Indonesian constitution upholds the availability of human resources to be educated for social change. The advancement of educational facilities creates inequality among human resources in accessing a better education. This inequality creates social reproduction through the educational system. The iron cage of the educational system chains the production of potential leaders for social change. The sociological method is conducted to analyze andevaluate the root of the problem to bring in the emic perspective. This method accesses books, articles, journals, and academic writing. This research aims to align local cultural values, Siri Na Pacce, to construct leadership values in generating an accessible educational system. To conclude, the construction of educational leadership is based on the solid value of Siri Na Pacce to build the character of being with others.